Patient-centered Fertility Care: From Theory to Practice - Fatemeh Jafarzadeh-Kenarsari; Ataollah Ghahiri; Ali Zargham-Boroujeni; Mojtaba Habibi; Maryam Hashemi (Mashhad University of Medical Sciences, 2016)
Background & aim: Healthcare areas, especially fertility care (commonly accompanied with high emotions, as well as long-term and recurring treatment periods) could exclusively benefit from patient-centered care (PCC). Despite evident advantages of PCC, this approach has not been practiced as a routine procedure in current clinical environments yet, even in western developed countries. Therefore, this review aimed to evaluate the significance and different aspects of PCC, while emphasizing on patient-centered fertility care, its challenges, and applicable recommendations in this regard. Methods: This narrative review was conducted on 29 relevant medical and clinical papers (published during 1990-2015) collected using various national and international databases (e.g., SID, Magiran, Medlib, Google scholar, Proquest, Pubmed, Wiley, Science direct, and Scopus). Key words and phrases used in this review were "infertility", "fertility care", "childlessness", "patient-centered care", "patient-centered fertility care" "shared decision-making", "infertile patient preferences", and "patient involvement in fertility care". Results: According to the literature, implementation challenges of patient-centered fertility care were reported as different individual and organizational factors. These factors include lack of professional motivation to change, underestimating the significance of patient-centeredness by healthcare professionals, difficulty in translation of feedback into concrete measures, lack of time and financial resources, insufficient experience of healthcare professionals with regard to identification of needs and preferences of patients, traditional organizational culture, and common misconceptions. Conclusion: Promotion of patient-centered fertility services requires the identification of infertile needs and priorities of individuals, designation of interventional and supportive programs based on sociocultural characteristics of the community to fulfill such preferences, and considering patients as the most significant stakeholders of each healthcare center. This review might provide important data for healthcare professionals and policymakers aiming to improve patient-centered fertility care.